Assessment of the application of cathodic stripping voltammetry to the analysis of diazo reactive dyes and their hydrolysis products - Guaratini, CCI; Fogg, A. G.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2001)
Two reactive dyes, C.I. Reactive Red 120 (RR120) and C.I. Reactive Green 19 (RG19), each bearing two azo groups as the chromophoric moiety and two monochloro-s-triazine groups as reactive groups, can be detected at nanomolar levels using cathodic stripping voltammetry. Linear calibration graphs were obtained for both reactive dyes, from 0.015 to 0.14 mu mol l(-1) for RR120 in pH 4 buffer and from 0.012 to 0.26 mu mol l(-1) for RG19 in pH 3 buffer, using a preconcentration at 0 V during 180 and 240 s on the mercury electrode, respectively. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: reactive dyes; cathodic stripping voltammetry; dye hydrolysis; dye determination